Pengembangan Model Pembelajaran “Taro Ada” (Stimulation, Reading, Analysis, Determine, Application) Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Marwidayanti Marwidayanti; Sirniawan Sirniawan; Muhiddin Palennari (Jurnal Biologi dan Pembelajarannya (JB&P), 2024)
This research aims to develop the "TARO ADA" learning model to improve students' critical thinking skills. This research is research and development research which refers to the 4-D model which has four stages, namely define, design, develop, disseminate. Data collection technique. The results of the development of the TARO ADA model are based on supporting learning theories. The TARO ADA learning model consists of 5 stages, namely Stimulation, Reading, Analysis, Determine, and Application.